Guidelines for the endoscopic nasal surgery during COVID-19 pandemic - Husain, Parvez; Ahmed, Shaheen Khalil; Husain, Benazeer (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
COVID-19, the respiratory illness caused by the novel SARS-CoV-2 virus has rapidly emerged as a serious global health concern. The world health organization (WHO) and has enacted various protocols for healthcare institutions internationally in an attempt to slow the spread of disease, including adjustments for procedures performed by otolaryngologists. Based upon published evidence we highlight different strategies to reduce infection transmission during endoscopic sinus surgery. All patients undergoing endoscopic sinus surgery should be discussed with health care staff to be involved in procedure. The patients should be divided into elective, semi-elective, and urgent/emergency. COVID-19 test should be done in all patients prior to surgery along with high resolution computed tomography (HRCT) chest. Irrespective of COVID screening results, it is advisable to treat all patients undergoing aerosol generating procedures as COVID-19 positive, and the whole theatre team should wear personal protection equipment (PPE) as per current national guidelines. Preoperative nasal decongestion to be undertaken with atomization devices. Consider telephone/video clinic follow up appointments unless clinical examination is considered essential. Considering the current health crisis caused by COVID-19, the following guidelines are recommended for performing nasal surgeries: patient visits must be limited to only urgent/emergent cases for the time being. Only vital personnel should remain in the OT while performing any nasal endoscopic procedure as this will both reduce exposure and conserve vital personal protective equipment. Five levels of protection are recommended for the person performing the procedure.